2018
DOI: 10.7150/ijbs.27197
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β/SMAD4-Regulated LncRNA-LINP1 Inhibits Epithelial-Mesenchymal Transition in Lung Cancer

Abstract: Lung cancer is the leading cause of cancer related deaths worldwide. TGF-β-induced epithelial-mesenchymal transition (EMT) is a key cell-intrinsic identity for tumor cell migration, invasion, and stemness acquisition in cancer metastasis. Long noncoding RNAs (lncRNAs) have not been fully investigated for their involvement in regulating TGF-β-induced EMT and metastasis in lung cancer. Here, we demonstrated that the transcription of lncRNA in nonhomologous end joining (NHEJ) pathway 1 (LINP1) was inhibited by TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…lncRNAs have been reported as potential prognostic biomarkers and important regulatory factors of many types of cancer, 25,26 including liver cancer, 27 BC, 28 and lung cancer 29 . It is evident that lncRNA has the ability to act as miRNA sponges, which functioned as endogenous miRNA sponges via binding with miRNA 30 .…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs have been reported as potential prognostic biomarkers and important regulatory factors of many types of cancer, 25,26 including liver cancer, 27 BC, 28 and lung cancer 29 . It is evident that lncRNA has the ability to act as miRNA sponges, which functioned as endogenous miRNA sponges via binding with miRNA 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Many of these lncRNAs are regulated by TGF-β. [11][12][13][14][15] LncRNAs play essential roles in the migration, invasion and EMT and are discovered to act as miRNA sponges to participate in cancer progression. [16][17][18] Our previous study has shown that six lncRNAs, including LINC02323, are associated with metastasis and prognosis of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has demonstrated that TGF-β-related lncRNAs play pivotal roles in the progression of tumorigenesis through regulating EMT. 36,37 During the process of EMT, epithelial markers (such as E-cadherin) are downregulated and mesenchymal markers (such as N-cadherin and vimentin) are upregulated. 38,39 In the present study, we confirmed that the expression of LOC440173 was associated with cell migration and invasion and that LOC440173 was upregulated in TGF-β-treated Eca109 cells.…”
Section: Discussionmentioning
confidence: 99%